DIVIDEND POLICY IN AUSTRALIA - Lukas Setia Atmaja (University of Merdeka Malang, 2009)
This study examined the determinants of dividends in an environment where taxwas supposedly a main reason for paying dividends. The imputation tax system in Australiahad led to the expectation that firms should pay the maximum possible franked dividends.Using panel data from January 1994 to December 2004, I found strong evidence that dividendpayout ratio and likelihood of paying dividends were positively related to ownershipconcentration, profitability, firm size, the presence of dividend reinvestment scheme and taxpaid, and were negatively related to leverage, growth opportunity, business risks and investment.My findings supported the conjecture that dividend policy could be explained by tax reasons,residual theory and agency relationship simultaneously.